EVALUATING THE PROPERTIES OF MASONRYBLOCKS BOUND WITH BITUMEN - Arya Thanaya, I Nyoman (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 2 Juli 2010)
This paper covers investigation which was carried out in the United Kingdom (UK), where utilization of waste materials in building industry had been encouraged in line with the UK government strategy to reduce waste disposal to landfill. The investigation was about building block named as Masonryblock, a masonry building block material that incorporates waste materials, namely steel slag, crushed glass, and coal fly ash, bound with bitumen (asphalt). The binder used was 50 pen bitumen. The materials were hot mixed, statically compacted then cured at 200°C for 24 hours. The main properties of the blocks evaluated were compressive strength, creep and volume stability due to moisture and thermal exposure. It was found that the Masonryblock compressive strength was comparable or even can exceed the compressive strength of concrete block commonly used in the UK (2.8-10 MPa), and can satisfy creep strain < 100 microstrain. The volume stability of the Masonryblock was found affected by moisture exposure. The samples expanded due to higher relative humidity and vice versa. On thermal exposure the samples expanded and the expansion was found highly reversible. The Masonryblocks gave coefficient of thermal expansion comparable to clay bricks.
Keywords: masonry, properties, bitumen, waste material. EVALUASI